2022
DOI: 10.1039/d2ee01149b
|View full text |Cite
|
Sign up to set email alerts
|

Spins at work: probing charging and discharging of organic radical batteries by electron paramagnetic resonance spectroscopy

Abstract: Organic radical batteries (ORBs) are a promising class of electrochemical power sources employing organic radicals as redox-active groups. This article reports on the development of a versatile on-substrate electrode setup...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…The first one allowed us to check plasmonic properties of the nanohybrids whereas the second one provides information on the nature and concentration of paramagnetic defects. The EPR experiments were performed on a laboratory-built spectrometer described in [ 49 ] (the main parameters are the following: modulation amplitude of 0.5 mT, modulation frequency of 100 kHz, microwave power attenuation of 20 dB, temperature of 100 K).…”
Section: Methodsmentioning
confidence: 99%
“…The first one allowed us to check plasmonic properties of the nanohybrids whereas the second one provides information on the nature and concentration of paramagnetic defects. The EPR experiments were performed on a laboratory-built spectrometer described in [ 49 ] (the main parameters are the following: modulation amplitude of 0.5 mT, modulation frequency of 100 kHz, microwave power attenuation of 20 dB, temperature of 100 K).…”
Section: Methodsmentioning
confidence: 99%
“…With respect to battery materials, continuous wave (CW) EPR is often used to confirm the presence of unpaired electrons and for quantification of radical density. 6,19,20 Moreover, pulsed EPR techniques, [21][22][23][24] in operando CW EPR 25 and EPR imaging 26,27 for battery research have also been demonstrated. PTMA based ORBs consist of nitroxide radicals as the redox active unit, which are well-characterised using EPR 28 at low concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…For ORBs with nitroxide radicals as redox units, in situ 30 and in operando 22 CW EPR have shown the presence of electrochemically inactive radicals on the cathode film. The presence of such inactive redox centres, which do not undergo a change in their redox states while charging or discharging, inhibits the maximum attainable capacity of the ORB.…”
Section: Introductionmentioning
confidence: 99%
“…One such technique is electron paramagnetic resonance (EPR) spectroscopy, which is used to study unpaired electron spins. EPR has so far been used in studying operando electrolyte phenomena in redox flow batteries 1 , 2 , 3 or fuel cell membranes, 4 , 5 but its utility in studying conductive solid-state materials such as electrocatalysts remains limited.…”
Section: Introductionmentioning
confidence: 99%